Neutral Inventions and Production Functions: an Addendum - Sato, R.; Beckmann, M. (Review of Economic Studies, 1968)
R. Sato, M. Beckmann; Neutral Inventions and Production Functions: an Addendum, The Review of Economic Studies, Volume 35, Issue 3, 1 July 1968, Pages 366,